Autoestima y funcionamiento familiar en el establecimiento del proyecto de vida en adolescentes de la institución educativa Cesar Vallejo Trujillo - Corcuera Picchón, Cinthia Arlé (2010)
The present research, correlational descriptive type and cross section, was made in the Public Educative Institution “Cesar Vallejo” of the destrict Trujillo, 2010, in order to determine the relation that exist between the self-esteem and the familiar functioning in the life project establishment in adolescents. The sample was constituted by 160 adolescents from third, fourth and fifth year of secondary. For the data collection 3 instruments were used: Selfesteem test school form of Coopersmith, Scale of real and ideal familiar functioning of Olson and Scale rating of life project. The obtained data was processed and analyzed in SPSS version 17 statistical tables and presented in a double entry and absolute and percentage frequencies. To determine the relationship between variables using Chi Square statistical test, the results indicated that: the 60.4 percent of the adolescents show half self-esteem, the 48.8 percent of the adolescents show a high familiar functioning and the 65.0 percent of the adolescents show a defined life project. Between higher is the level of self-esteem, higher is the probability of life project establish. There exist meaningful relation between the level of self-esteem and the life project establishment in adolescents. P= 0.002 <0.05. There isn´t exist meaningful relation between the familiar functioning and the life project establishment in adolescents. P= 0.201 >0.05. There also exists meaningful relation between the level of self-esteem and the familiar functioning in the life project establishment in adolescents. P= 0.0274 <0.05.